Structural analysis of the Lutzow-Holm Complex in Akarui Point, East Antarctica, and overview of the complex - Ikeda,Takeshi; Kawakami,Tetsuo (National Institute of Polar Research, 2004)
P(論文) Two phases of major deformation are responsible for the dominant structures at Akarui Point, Prince Olav Coast, East Antarctica. The first phase, referred to as D_(m-1), is associated with the formation of foliation defined by biotite and hornblende aligned sub-parallel to compositional layering. The foliation is locally parallel to the axial planes of isoclinal and intrafolial folds of gneissic layers. Boudins are present with long axes subparallel to the axes of F_(m-1) folds. A second phase of deformation, denoted as D_m, produced a crenulation lineation and axial planar foliation that trends NW-SE throughout the area. This foliation is parallel to the axial plane of the large-scale Akarui Point Synform, which has a fold axis plunging gently SE, suggesting that the Akarui Point Synform formed during D_m. A locally-developed third phase of deformation (D_(m+1)) produced gentle folding of S_(m-1) and S_m. Chemical compositions of biotite grains that define S_(m-1) and S_m are similar. Migmatite shows close associations with D_(m-1) and D_m structures. This suggests that both phases of deformation were contemporaneous with high-grade metamorphism. Compilation of structural data in other areas reveals that D_(m-1) and D_m controlled dominant structures of the Lutzow-Holm Complex. Several folding events after D_m may be responsible for differing orientations of D_m structures between localities. departmental bulletin paper